DESAIN JARINGAN WIRELESS MENGGUNAKAN DISTRIBUTION SYSTEM (WDS) DAN PENGUJIAN BERDASARKAN QUALITY OF SERVICE (QOS) - Muchamad Rusdan; Muhamad Sabar (Universitas Widyatama, 2019)
The purpose of this research is to design a wireless network that utilizes wireless lines as a backbone on all access points except the base station point that still uses UTP cable as its backbone and expands the coverage area of ??wireless networks that are able to cover all parts of Widyatama University. The results of wireless network design with WDS will be tested by simulating. Then testing will be focused on parameters of delay, packet loss, throughput, and jitter using the Quality of Service (QoS) method using the Axis netTools application. Wireless network design with Wireless Distribution System (WDS) has a better level of flexibility than a backbone that uses Unshielded Twisted Pair (UTP) cable. The test results show that throughput, delay, packet loss, and jitter show good results. Throughput test results obtained an average value of throughput with a percentage of 90%, can be categorized GOOD with index 3, while the delay test results obtained an average value of 107.8 can be categorized VERY GOOD with index 4, then the average value of packet loss with a percentage of 2%, can be categorized GOOD with index 3, and the results of the jitter test obtained varying values ??with an average value of jitter of 1.71 ms, can be categorized GOOD with index 3.